Strong Aerosol Effects on Cloud Amount Based on Long‐Term Satellite Observations Over the East Coast of the United States. Issue 6 (26th March 2021) - Cao, Yang; Wang, Minghuai; Rosenfeld, Daniel; Zhu, Yannian; Liang, Yuan; Liu, Zhoukun; Bai, Heming
Abstract: Here, we use 16‐year satellite and reanalysis data in combination with a multivariate regression model to investigate how aerosols affect cloud fraction (CF) over the East Coast of the United States. Cloud droplet number concentrations (Nd ), cloud geometrical thickness, lower tropospheric stability, and relative humidity at 950 hPa (RH950 ) are identified as major cloud controlling parameters that explain 97% of the variability in CF. Nd is shown to play an important role in regulating the dependence of CF on RH950 . The observed annual‐mean CF shows no significant trend due to the cancellation from the opposite trends in Nd and RH950 . The multivariate regression model revealed that the decline in Nd alone would lead to about a 20% relative decline in CF. Our results indicate the significant aerosol effects on CF and suggest the need to account for pollution‐induced cloud changes in quantifying cloud feedback based on long‐term observations. Plain Language Summary: Understanding how aerosols affect cloud cover is critical for reducing the large uncertainty of the radiative forcing associated with aerosol‐cloud interactions for future climate projections. By choosing a region (East Coast of the United States) that has experienced a significant decline in cloud droplet number concentrations due to pollution control in recent decades, we quantify aerosol effects on cloud amount based on long‐term satellite observation and reanalysis data in combination with a statistical regression model that isolates aerosol effects from meteorology influences. Our results reveal significant effects of aerosols on cloud amount and indicate the need to account for changes in cloud microphysics for constraining and quantifying cloud feedback based on long‐term observations. Key Points: Nd plays an important role in regulating the dependence of cloud fraction (CF) on RH950 The observed annual‐mean CF shows no significant trend due to the cancellation from the opposite trends in Nd and RH950 When fixing the meteorology, we found significant aerosol effects on cloud amount based on long‐term satellite observations